The Effect of Exposure to Formaldehyde Vapor on the Structure of Testes in the Rabbits. - Al-Hubaity, Abduljabar Y. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: This study has been performed to detect any structural changes in the testes of rabbits that have been exposed to formaldehyde vapor.Materials and Methods: Eighteen male rabbits has been used in this study, 12 of them were exposed to formalin vapor for 2 month, while the other 6 were exposed to the vapor of distilled water for 2 month too. All animals were killed at the end of experiments, and then pieces of testes were prepared for light microscopic examination. Sections were collected from the paraffin wax blocks and stained by H & E and finally examined by Olympus light microscope.Results: Most of the seminiferous tubules from the formaldehyde exposed group were atrophied with no evidence of spermatogonia and lined only by Sertoli cells, in addition some sections showed multinucleated giant cells.Conclusions: This is the first study to report that formaldehyde induces damage to spermatogenesis without a reduction in the number of Sertoli cells and Spermatogenic damage can be seen in most of the formaldehyde exposed rabbits.